A Case Series of 18 Congenital Haemangiomas: Clinical, Histological and Ultrasound Features, and their Relationship with Complications and Atypical Behaviour - Gloria Juan-Carpena; Juan Carlos Palazón-Cabanes; Paloma Tallón-Guerola; Maria Niveiro-De Jaime; Isabel Betlloch-Mas (Medical Journals Sweden, 2023)
Recent studies have advanced our understanding of the clinical, histological and imaging characteristics of congenital haemangiomas (CHs), and have reported possible complications and atypical behaviour. The aim of this study is to describe the clinical, histological and ultrasound features of a series of CHs and to analyse their association with complications and atypical behaviour, with a view to providing diagnostic and management recommendations. The medical records, histology results and ultrasound images of all patients with CH diagnosed in the Dermatology Department of Alicante University General Hospital between 2006 and 2021 were retrospectively reviewed. A total of 18 patients were included, of whom 4 (22.2%) had complications. The most severe was 1 case with heart failure. There was a significant association between large CH size (> 5 cm) and the occurrence of complications (p = 0.019). The study identified 3 different lobule patterns, but found no relationship with CH subtype or other findings. The associations of venous ectasia, venous lakes and arteriovenous microshunts with occurrence of complications was borderline significant (p = 0.055). Study limitations were the small sample and the retrospective analysis. To conclude, haematological and cardiological assessment is indicated in large CHs and should be considered in CHs with ultrasound findings of venous ectasia, venous lakes or arteriovenous microshunts, as these cases present a greater risk of complications.